Temperature dependence of the spontaneous emission mechanisms of localized-state heterosystem - Lee, Jiunn-Chyi (Oficyna Wydawnicza Politechniki Wrocławskiej, 2011)
The temperature dependent photoluminescence (PL) spectra measured from localized-state material system is presented. Two localized-state heterosystems, including InGaN/GaN multi-quantum well (MQW) and InAs/GaAs quantum dot (QD) samples were prepared. The samples were investigated both experimentally and theoretically. It has been found that the temperature dependence of the PL peak energies from both samples behaves differently. S-shaped and anti-S-shaped PL peak energies have been observed for MQW and QD samples, respectively. We present a model which takes into account all of the key factors for the localized-carrier dynamics. The model is applied to interpret the experimental data obtained from the two kinds of material systems. Detailed discussion concerning this model provides an explicit interpretation that it is the difference in the electronic structure of the two material systems that leads to the significantly different temperature dependence of their luminescence bands.
Optica Applicata, Vol. 41, 2011, Nr 4, s. 911-919
Keywords: optyka; quantum dot; multi-quantum well; photoluminescence; localized-state